THE EFFECT OF INQUIRY TRAINING LEARNING MODELS USING MACROMEDIA FLASH ON STUDENTS LEARNING OUTCOMES OF PHYSICAL SUBJECT - Sri Arfani Hs; Sehat Simatupang (UNIVERSITAS NEGERI MEDAN, 2020)
This study aims to determine the effect of the inquiry training learning model using macromedia flash on student learning outcomes on momentum and impulse material in class X semester II Teladan Medan academic year 2017/2018. This type of research is a quasi experiment with two group research designs pre-test and post-test. The population in the study were all students of class X Senior High School Teladan Medan. Sampling was done by random sampling, namely class X-3 as an experimental class by applying the inquiry training learning model using macromedia flash and class X-2 as a control class that applies conventional learning, each class consists of 40 students. The instrument used was in the form of a multiple choice test of 15 questions that had been validated by the validator and student activity observation sheets in the experimental class and the control class. The results of pre-test data processing showed that the pre-test mean value of the experimental class was 31.83 and the control class was 30.49, the post-test average value of the experimental class was 75.33 and the control class was 64.83. The average score of the experimental class student activity reached 66.72% in the active category and the control class reached 54.50% in the less active category. The results obtained show that there was an effect of the inquiry training learning model using macromedia flash on student learning outcomes on momentum and impulse material in class X Senior High School Teladan Medan academic year 2017/2018.